1993
DOI: 10.1103/physrevb.48.10047
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between interatomic distances and the x-ray-absorption near-edge structure of single-crystal sapphire

Abstract: The high-resolution Al L-edge x-ray-absorption near-edge structure from single-crystal sapphire has been recorded by measuring the total-electron yield and x-ray-fluorescence yield with synchrotron radiation. The edge structures up to 11 eV from the absorption edge are assigned in terms of the transitions of Al 2p electrons to empty levels using molecular-orbital calculations. The post-edge features between 11 and 60 eV above the Al L» absorption edge were found to correlate very well with the interatomic dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Peak a (doublet) in the FY spectrum is due to the transition of electrons from the 2p to 3s-like a orbitals in metallic aluminum and peak b, in the TEY spectrum is the corresponding transition for aluminum oxide. Broad peak c, is due to the transition of electrons to 3p-like t orbitals of aluminum oxide species [63]. It can be observed that the TEY spectrum of the antiwear film shows the presence of both metallic aluminum and aluminum oxide species; whereas the FY spectrum show mostly metallic Al and a trace of aluminum oxide, in contrast to Si (figure 3(a), bottom).…”
Section: Macro Xanes Analysis Initial Stages Of Wearmentioning
confidence: 91%
“…Peak a (doublet) in the FY spectrum is due to the transition of electrons from the 2p to 3s-like a orbitals in metallic aluminum and peak b, in the TEY spectrum is the corresponding transition for aluminum oxide. Broad peak c, is due to the transition of electrons to 3p-like t orbitals of aluminum oxide species [63]. It can be observed that the TEY spectrum of the antiwear film shows the presence of both metallic aluminum and aluminum oxide species; whereas the FY spectrum show mostly metallic Al and a trace of aluminum oxide, in contrast to Si (figure 3(a), bottom).…”
Section: Macro Xanes Analysis Initial Stages Of Wearmentioning
confidence: 91%
“…2. The Al L-edge spectra of different types of Al oxides and AlPO 4 have been reported using ELNES (Jiang et al, 2002;Bouchet and Colliex, 2003) and XANES (Chen et al, 1993). For minerals that are well crystalline, the first transition in the Al L-edge is usually split into two peaks with a separation of 0.45 eV [e.g., a-Al 2 O 3 (Chen et al, 1993) and AlPO 4 (personal communication with G.S.…”
Section: Al L-edge Studymentioning
confidence: 98%
“…The post-edge minimum feature is a consequence of multiple-scattering phenomena which have been shown to be dependent on interatomic distances and angles [30][31][32].…”
Section: Xanes Spectramentioning
confidence: 99%